2021
DOI: 10.3390/membranes11080558
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Up and Long-Term Study of Electrodialysis with Ultrafiltration Membrane for the Separation of a Herring Milt Hydrolysate

Abstract: Electrodialysis with ultrafiltration membrane (EDUF) was selected to separate a herring milt hydrolysate (HMH) in a scale-up and long-term study for the recovery of bioactive peptides. The scale-up was performed to maximise peptide recovery by placing a total membrane area of 0.08 m2 for each anionic and cationic compartment. Twelve consecutive runs were carried out, for a total of 69 h, with minimal salt solution cleaning in between experiments. The final peptide migration rate showed that cationic peptides h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The HMH1 supplementation contained significantly more peptides than the other two supplements with a concentration of 93.79% [ 18 ]. However, the HMH1 peptides had a lower molecular weight than those of the HMH2 and HMH5 supplements (62% of HMH1 peptides had a molecular weight higher than 10,000 Da, while all HMH1 peptides were smaller than 1000 Da), since the HMH1 product was the permeate and the HMH2 product was the retentate [ 16 , 19 ]. Also, the previous studies from Durand et al [ 16 , 17 , 18 ] showed that these three supplements had the same free amino acids, but in different concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HMH1 supplementation contained significantly more peptides than the other two supplements with a concentration of 93.79% [ 18 ]. However, the HMH1 peptides had a lower molecular weight than those of the HMH2 and HMH5 supplements (62% of HMH1 peptides had a molecular weight higher than 10,000 Da, while all HMH1 peptides were smaller than 1000 Da), since the HMH1 product was the permeate and the HMH2 product was the retentate [ 16 , 19 ]. Also, the previous studies from Durand et al [ 16 , 17 , 18 ] showed that these three supplements had the same free amino acids, but in different concentrations.…”
Section: Resultsmentioning
confidence: 99%
“… EDUF configuration used for the separation and production of HMH4 and HMH5; P +/− neutral peptides, P + cationic peptides, P − anionic peptides [ 19 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…As a new method, this technology confers various advantages during extraction of NSS, energy saving, high single-stage separation efficiency, environmental protection, no phase change, and a simple filtration process, among others (55). At present, a variety of membrane separation and extraction processes, such as ultrafiltration (UF), nanofiltration, electrodialysis, pervaporation and gas separation have been developed (56)(57)(58)(59)(60). Firstly, processes for separation and purification of alkaloids are greatly constrained by various challenges, including high pollution, high energy consumption and low continuity.…”
Section: Membrane Extraction Methodsmentioning
confidence: 99%